Super Dye Adsorption Capability of Natural Superfine Down Particles for Organic Contaminant from Binary Dye Mixture (Journal of Fiber Bioengineering and Informatics, 2019)
Reuse of waste resources is still a challenging issue for public health and ecosystem protection. Herein, natural superfine down particles (NSDP) were successfully prepared from the wasted down fibers and investigated for the removal of methylene blue (MB) and methyl orange (MO) dyes from the binary dye solution. The adsorbent was characterized by scanning electron microscopy (SEM) and N2 adsorption. The adsorption behavior of NSDP for these two dyes was investigated as a function of pH. The results showed that the NSDP surface has surface area of 7 277 cm2/g and an abundance of functional groups (carboxyl, hydroxyl and amine-groups). The adsorption capacity of NSDP was strongly pH-dependence. The results indicated that NSDP can be used as an efficient and economic adsorbent to remove dyes in the textile effluents.
Keywords: Natural Superfine Down Particle; Textile Wastewater; Dye Adsorption; pH